1997
DOI: 10.1046/j.1365-3059.1997.d01-75.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of resistance inducers, free‐radical scavengers and an antagonistic strain of Pseudomonas fluorescens for control of Rhizoctonia solani AG‐4 in bean and cucumber

Abstract: Sixteen chemicals from different groups of known resistance inducers were tested as a soil drench in a humosoil : sand mix infested with an isolate of Rhizoctonia solani AG‐4. Among these, 5‐nitrosalicylic acid (2 mM aqueous solution), o‐acetylsalicylic acid (2 mM), 2,6‐dichloroisonicotinic acid (0.25 mM), 2‐aminoisobutyric acid (2 mM) and lichenin (2 mM) controlled pre‐emergence damping‐off and post‐emergence seedling mortality of bean cv. Dufrix, but gave little or weak and variable disease control in cucumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
0
4
0
3
Order By: Relevance
“…Resultado contrariofoi observado utilizando ASM na concentração de 2 mM, a qual reduziu em 50% o crescimento micelial de R. solani (KATARIA et al,1997).…”
Section: Caracterização Histórica Da Cultura E Prognóstico De… Historunclassified
See 1 more Smart Citation
“…Resultado contrariofoi observado utilizando ASM na concentração de 2 mM, a qual reduziu em 50% o crescimento micelial de R. solani (KATARIA et al,1997).…”
Section: Caracterização Histórica Da Cultura E Prognóstico De… Historunclassified
“…A partir da descoberta do ASM, foi dado um grande passo no campo da indução de resistência, já que o composto deu o impulso necessário para que empresas se interessassem na fabricação de produtos a partir de compostos passíveis de serem patenteados (SOBRINHO et al, 2005). KATARIA et al (1997), observaram que o ASM na concentração de 2 mM reduziu em 50% o crescimento micelial de Rhizoctoniasolani. Em tomateiro a aplicação de ASM em conjunto com fungicidas (ASM + mancozeb alternado com difenoconazole e azoxystrobin) reduziu a severidade da doença pintapreta causada por Alternaria solani (TOFOLI e DOMINGUES, 2005).…”
Section: Introductionunclassified
“…The AS regulates the resistance mechanisms in the infection location through the systemic acquired resistance (RSA), which results on the synthesis of the phytoalexins and the PR proteins (HEIL; BOSTOCK, 2002). KATARIA et al (1997), observed that the salicylic acid and the chloro-salicylic acid inhibited 100% of the mycelial growth of Rhizoctonia solani in the concentration of 10 mM, while the acibenzolar-Smethyl reduced in 50% in the concentration of 2 mM.…”
Section: Printmentioning
confidence: 99%
“…Possibly, this result is related to the concentration studied, since in assessing the effect of AS under more elevated concentrations, it was observed that under the concentration of 10 mM, occurred 100% inhibition of mycelial growth of R. solani (KATARIA et al, 1997). According to Kuć (2001), the resistance inducers can present fungitoxic effect, depending on the concentration used and the pathogen assessed.…”
Section: Concentration Of As (Mm)mentioning
confidence: 99%
“…O fungicida tebuconazole inibiu totalmente o crescimento micelial em todas as doses testadas. Kataria et al (9) observaram que o ASM na dose de 2mM reduziu em 50% o crescimento micelial de Rhizoctonia solani, enquanto que o ácido salicílico e o ácido clorosalicílico inibiram 100% do crescimento micelial na dose de 10mM. Grant et al (7) também observaram redução do crescimento micelial de isolados de Phytophthora infestans com dosagem a partir de 1mM de fosfito.…”
unclassified